Structural Engineering's Readiness to Face the Challenges of Natural Disasters in the 21st Century - Lie Jie; Xie Guilin; Deng Jiao (Journal of Moeslim Research Technik, 2024)
Research Background: In the modern era, the challenges of natural disasters are increasing as a result of climate change and uncontrolled development. Therefore, structural engineering preparedness in the face of natural disasters is crucial to minimize losses and negative impacts. This research aims to investigate structural engineering preparedness in facing the challenges of natural disasters in the 21st century. This is done by analyzing technical approaches, regulations, and innovations in structural engineering that can improve the resilience of infrastructure to natural disasters. The research methods used include literature review, policy analysis, and interviews with structural engineering experts. Data were collected and analyzed to understand recent developments in structural technology that can cope with natural disasters, and to evaluate the successful implementation of regulations and best practices. The results showed that structural engineering has undergone significant developments in dealing with natural disasters in the 21st century. Approaches such as anti-earthquake design, sensor technology for structural monitoring, and construction of disaster-resistant infrastructure have helped improve the resilience of infrastructure to natural disasters. From the results of this study, it can be concluded that the readiness of structural engineering to face the challenges of natural disasters in the 21st century has improved significantly. However, further efforts in technology development, regulation, and public awareness are still needed to ensure more resilient infrastructure against natural disasters in the future.